Analisis Implementasi Manajemen Kinerja terhadap Peningkatan Kinerja Pegawai dan Kualitas Pelayanan di RSUD Dr. Adnaan WD Payakumbuh - Silvia Harilona; Almasdi, Almasdi (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
This study was motivated by the gap between employee performance evaluations and the quality of health services at Dr. Adnaan WD Payakumbuh Regional General Hospital. Although the majority of employees received a “Good” performance rating through the e-Kinerja system and SKP, the public still complained about slow service, long lines, a lack of empathy among staff, and poor coordination between units. This study aims to analyze the implementation of performance management in relation to improvements in employee performance and the quality of healthcare services. The research method employs a descriptive qualitative approach, utilizing data collection techniques such as in-depth interviews, observations, and documentation involving hospital management, medical and non-medical staff, as well as patients. Data analysis utilizes the Miles and Huberman model through data reduction, data presentation, and drawing conclusions. The results indicate that the implementation of performance management is not yet optimal because it remains administratively oriented and has not been integrated with service quality. Issues were identified in the areas of human resources, facilities, coordination, supervision, as well as low levels of empathy and service responsiveness. The study concludes that the performance management system does not yet fully support improvements in the quality of healthcare services; therefore, an evaluation based on service outcomes and patient satisfaction is required.